Pengaruh Dinning Atmosphere McDonald’s terhadap Keputusan Pembelian Gen Z: Survey Pelanggan McDonald’s Cabang Galuh Mas Karawang - Anisa Lestari; Kelsha Berliana Rifty; Abdul Yusuf (Economic Reviews Journal, 2024)
Environmental Influences and Purchasing Decisions at McDonald's Galuh Mas Branch, Karawang. This study aims to explore the influence of the environment and atmosphere on the purchase decision process of McDonald's Galuh Mas Branch, Karawang. The research method used is quantitative research. The population of this study was all Gen-Z consumers who bought and enjoyed food at McDonald's Galuh Mas Karawang Branch, with a total sample of 104 people. Data analysis is carried out using.